An automated software system to promote anticoagulation and reduce stroke risk: cluster-randomized controlled trial - Holt, Tim A.; Dalton, Andrew; Marshall, Tom; Fay, Matthew; Qureshi, Nadeem; Kirkpatrick, Susan; Hislop, Jenny; Lasserson, Daniel; Kearley, Karen; Mollison, Jill; Yu, Ly-Mee; Hobbs, F.D. Richard; et al. (American Heart Association, 2017)
Background and Purpose: Oral anticoagulants (OAC) substantially reduce risk of stroke in atrial fibrillation, but uptake is suboptimal. Electronic health records enable automated identification of people at risk but not receiving treatment. We investigated the effectiveness of a software tool (AURAS-AF [Automated Risk Assessment for Stroke in Atrial Fibrillation]) designed to identify such individuals during routine care through a cluster-randomized trial.